Rasch model for the need assessment instrument of academic guidance and counseling program in junior high school - Farozin, Muh; Astuti, Budi; Sanyata, Sigit; Titi, Dwitias; Nurmalasari, Ela; Sutanti, Natri (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
Developing an instrument for the need for academic guidance and counseling topics is a strategic step to support the needs assessment carried out by guidance and counseling teachers and counselors in schools. The development of this instrument had been carried out by Arfalah using exploratory factor analysis. This study aims to analyze the instrument using the Rasch model. The research procedure began with collecting data from two integrated online needs assessments of academic guidance and counseling instruments. The content validity test involved six experts, and the field test involved 111 students from three junior high schools in Yogyakarta. Data were analyzed using Winsteps version 3.73 according to Fisher's five criteria for a good instrument. The content validity test showed Aiken's coefficient of 0.71, considered in the high category. Meanwhile, the results of the Rasch test showed the item response model. The analysis also indicated high reliability on both instruments above 0.90 and Cronbach's alpha value of 0.98. Five items were decided to be maintained based on the misfit test explored. The accuracy and focus of the instruments in revealing the need for academic guidance and counseling topics for high school students indicated a number above 40% and a fairly good level of instrument contamination, which was below 10%.